Integration of Waste Management and Environmental Impact Assessment for Sustainable Manufacturing in Sukolego Tofu Production - P.A. Islami, Mega Cattleya; Harnaningrum, Rizky Novera (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2025)
The tofu production process, particularly in small- to medium-scale industries like Sukolego Tofu Production, generates various types of waste that pose environmental challenges. This study aims to integrate waste management practices and environmental impact analysis within a sustainable manufacturing framework. This study uses a quantitative method with a causal associative approach to measure Waste Management (X1), Environmental Impact Assessment (X2), and Sustainable Manufacturing (Y). Data was collected through questionnaires distributed to 50 people living around the Sukolego Tofu Factory.  Data that meets the validity, reliability, and classical assumption tests is processed to produce a linear regression equation. The analysis results indicate that the Environmental Impact Assessment (EIA) variable has a positive and significant effect on Sustainable Manufacturing, both partially and simultaneously. However, the Waste Management variable does not exhibit a significant effect. This is supported by the significance (Sig.) values, where the EIA variable yields a value of 0.004 (p < 0.05), indicating statistical significance, whereas the Waste Management variable yields a value of 0.702, which is not statistically significant.